Astrocytes with previous chronic exposure to amyloid β‐peptide fragment 1–40 suppress excitatory synaptic transmission. Issue 6 (10th November 2017) - Kawano, Hiroyuki; Oyabu, Kohei; Yamamoto, Hideaki; Eto, Kei; Adaniya, Yuna; Kubota, Kaori; Watanabe, Takuya; Hirano‐Iwata, Ayumi; Nabekura, Junichi; Katsurabayashi, Shutaro; Iwasaki, Katsunori
Abstract: Synaptic dysfunction and neuronal death are responsible for cognitive and behavioral deficits in Alzheimer's disease (AD). It is well known that such neurological abnormalities are preceded by long‐term exposure of amyloid β‐peptide (Aβ) and/or hyperphosphorylated tau prior. In addition to the neurological deficit, astrocytes as a major glial cell type in the brain, significantly participate in the neuropathogenic mechanisms underlying synaptic modulation. Although astrocytes play a significant key role in modulating synaptic transmission, little is known on whether astrocyte dysfunction caused by such long‐term Aβ exposure affects synapse formation and function. Here, we show that synapse formation and synaptic transmission are attenuated in hippocampal‐naïve neurons co‐cultured with astrocytes that have previously experienced chronic Aβ1‐40 exposure. In this abnormal astrocytic condition, hippocampal neurons exhibit decrements of evoked excitatory post‐synaptic currents (EPSCs) and miniature EPSC frequency. Furthermore, size of readily releasable synaptic pools and number of excitatory synapses were also significantly decreased. Contrary to these negative effects, release probability at individual synapses was significantly increased in the same astrocytic condition. Taken together, our data indicate that lower synaptic transmission caused by astrocytes previously, and chronically, exposed to Aβ1–40 is attributable to a small number of synapses with higher release probability. Abstract : Astrocytes are the major glial cell type of the brain, and among their many roles are involved in amyloid β (Aβ) clearance and synapse function. Aβ1‐40 ‐exposed astrocytes lead to reduced glutamatergic synaptic transmission, but enhanced synapse function at the individual level. This suggests that astrocytic pathological changes induced by long‐term Aβ1‐40 treatment may adversely affect neurotransmission in AD brain.